Relação entre periodontite apical, microbiota intestinal e alterações metabólicas em ratos : determinação de biomarcadores - Tavares, Cauana Oliva (2017)
Infection and dysbiosis present a close relationship with metabolic diseases, although the influence of apical periodontitis (AP) in this context needs further investigation. This thesis includes a review and an experimental study that evaluated the influence of AP in a rat model of metabolic disorder induced by 10% fructose supplementation. 60 male Wistar rats were used. Animals that received high fructose diet (HFD; N=30) or filtered water (control; N=30) were subdivided into additional groups: (i) without induction of AP (N=20); (ii) with AP induction 2 weeks before euthanasia (14 days; N=20); (iii) with AP induction 4 weeks before euthanasia (28 days; N=20). HFD triggered obesity-related type2 diabetes, as indicated by induction of overweight and hyperglycemia, besides polydipsia, regardless of the AP induction. There was no variation in the serum or intestinal levels of TNF, IL-1β and IL-6 among the experimental groups. Serum leptin and adiponectin levels were significantly elevated in the HFD group, without AP induction. The intestinal levels of leptin were significantly increased in the groups with 28 days of AP induction, despite HFD. A significant elevation of liver glutathione levels was observed in animals submitted to HFD and AP for 14 days. AP induction (14 or 28 days) led to pulp and periapical tissue inflammation, without any influence of HFD. Either HFD or AP induction led to dysbiosis, as indicated by a significant reduction of fecal A. muciniphila expression. Conluding, we provide novel evidence that AP can have systemic impacts on metabolic disorders, likely by modulating intestinal metabolism and microbiota.